The Impact of Selenium on the Physiological Activity of Yeast Cells Saccharomyces cerevisiae ATCC 7090 and Rhodotorula glutinis CCY 20-2-26 - Wioletta Sęk; Anna M. Kot; Marek Kieliszek (Frontiers in Bioscience-Landmark)
Background: This study investigated the selenium-binding capacity of the biomass of two yeast strains, Saccharomyces cerevisiae American Type Culture Collection (ATCC) 7090 and Rhodotorula glutinis CCY 20-2-26. Methods: The studies carried out methods of bioaccumulation by yeast biomass. Inorganic selenium was added to the culture media as an aqueous solution of Na2SeO3 at concentrations ranging from 0 to 40 mg Se4+/L. Results: The addition of selenium at concentrations >0.5 mg/L significantly reduced biomass yield compared with the control in the case of S. cerevisiae. A significant reduction in the biomass of R. glutinis was observed only at selenium doses >30 mg/L. The study found that for S. cerevisiae, cultivation should occur for 24 h in a medium with an initial selenium concentration of 20 mg/L to achieve the most efficient selenium accumulation by the yeast biomass. Under these conditions, the yeast could accumulate 4.27 mg Se4+/g. For the red yeast R. glutinis, optimal selenium binding conditions were achieved by cultivating for 48 h in a medium with an initial selenium ion concentration of 40 mg/L. This yeast strain was more resistant to high selenium doses, accumulating 7.53 mg Se4+/L at the highest tested dose (40 mg Se4+/L). Selenium supplementation of the medium from 20 mg Se4+/L and cultivation for 72 h caused significant changes in the morphology of S. cerevisiae cells (e.g., increased surface area compared with the control). Selenium doses of 20–40 mg/L after 48 h of cultivation significantly reduced the surface area compared with the control results for R. glutinis cells. Conclusions: Selenium significantly impacted carotenoid pigment production, with levels decreasing as the selenium concentration in the medium increased. Furthermore, selenium in the tested concentration range increased protein content in the cellular biomass but did not affect intracellular lipid production.